MoCoA: Customisable middleware for context-aware mobile applications - CAHILL, VINNY; BOUROCHE, MELANIE (My University, 2006)
Many programming models have been proposed to facilitate the development of context-aware applications. However, previous work does not offer support for building customised systems and has largely been targeted at a single application domain. In this paper, we describe MoCoA, a flexible middleware framework that permits the rapid development of context-aware applications and supports deployment scenarios ranging from augmented artefacts to city-wide smart-space applications. Crucially, MoCoA supports a small set of programming abstractions that are suitable for building a wide range of context-aware applications for deployment in a fixed or (ad hoc) mobile environment. For each of these abstractions, MoCoA provides a set of implementations via a library of components. We present three applications of the MoCoA framework that demonstrate both the use of the programming abstractions and the flexibility of the framework.
PUBLISHED
Keywords: Computer Science